Pattern of Coronary Artery Diseases (CAD) in patients under 40 Years of Age with Acute Coronary Syndrome (ACS) - Farooqui, Khadija Sarwat; Batool, Zakra; Muneer, Romaza; Abdullah Zahid, Khawaja; Riaz, Muhammad Hamza; Attiq, Amna (Indus Journal of Bioscience Research, 2024)
ObjectivesTo assess angiographic patterns, risk factor profile, and outcome of patients below 40 years of age with acute coronary syndrome undergoing coronary angiography for confirmed CAD.Materials and MethodsThe present study was an analytical cross-sectional study in a tertiary care hospital, and all the participants were ≤40 years old with new-onset ACS. Demographic variables, cardiovascular risk factors, and angiographic characteristics were assessed. They were evaluated for other cardiovascular risk factors and stratified according to the patterns of CAD on angiography.ResultsDepending on the localization of atherosclerotic lesions, 72% of patients were characterized by single-vessel coronary involvement with predominant damage to the left anterior descending artery. A smoking history, 68% dyslipidemia, 59% known history of CAD in first-degree relatives, and 52% were the most common risk factors. Most patients had normal left ventricular systolic performance. Nevertheless, 16% of patients would have poor follow-up results.ConclusionThe majority of young patients with ACS have single-vessel CAD, and conventional atherosclerotic risk factors contribute to the development of early-onset CAD. Prevention strategies, as well as CAD screening in this age group, are critical to avoid high incidences within this group.